Removing fermion doublers in chiral gauge theories on the lattice - FROLOV, SERGEY (Elsevier, 1994)
A method for removing fermion doublers in anomaly free chiral gauge theories on the lattice is proposed. It is proven that the resulting continuum theory is gauge invariant and does not require noninvariant counterterms of fine tuning of parameters.
PUBLISHED
Keywords: Mathematics; Gauge theory